Determination Oxidant - Antioxidant Enzyme and some Trace Elements in Breast Cancer in Baghdad City (Baghdad Science Journal, 2025)
level of effectiveness of Glutathione - S - Transferees (GST), Glutathione peroxides (GPX),Malondialdehyde (MDA) the product of lipid peroxidation and some trace elements ( zinc,seleinum,iron ,copper ) had been measured in sera of (50) women with breast disease.which had been divided to :Control group (25),The first group (A) benign breast tumors (25),the second group (B) breast cancer (25). The results showed a clear moral high level of Glutathione - S - Transferees (GST), Glutathione peroxidase (GPX) , and Malondialdehyde (MDA) level in breast cancer group while a slight increase were observed in the levels of these enzymes and(MDA) in benign breast group. A significant reduction was evident in the levels of selenium and zinc when compared with the control group while there were an increase in levels of sera copper , iron in the breast cancer group.As in (tissue) group of breast cancer found a rise in the level of selenium, zinc, copper, iron, compared with (serum) of breast cancer.